A trophic bottleneck?: The ecological role of trout‐perch Percopsis omiscomaycus in Saginaw Bay, Lake Huron. (8th October 2012) - Blouzdis, C. E.; Ivan, L. N.; Pothoven, S. A.; Roswell, C. R.; Foley, C. J.; Höök, T. O.
Summary Trout‐perch are abundant in many North American aquatic systems, but the ecological roles of trout‐perch as predators, competitors and prey remain relatively understudied. To elucidate the ecological role of trout‐perch in Saginaw Bay (Lake Huron, North America), the spatial and temporal diet composition was quantified and the frequency of occurrence of trout‐perch in diets of piscivorous walleye and yellow perch was evaluated. From May through November 2009–2010, trout‐perch and their potential predators and prey were collected monthly from five sites in Saginaw Bay using bottom‐trawls. Trout‐perch were abundant components of the Saginaw Bay fish community, and in 2009, represented 13.5% of fish collected in trawls, with only yellow perch (38%) and rainbow smelt (19.1%) being more common. Trout‐perch primarily consumed Chironomidae (84.0% of diet biomass) and exhibited strong, positive selection for Chironomidae and Amphipoda, suggesting that their diet preferences overlap with the economically important yellow perch and juvenile walleye. Energy content of trout‐perch averaged 4795 J g−1 wet and was similar to yellow perch (4662 J g−1 wet) and round goby (3740 J g−1 wet). Thus, they may provide a comparable food source for larger piscivorous fish. However, despite their high energy density, abundance, and spatial overlap with other fish prey species, trout‐perch were very rare in diets of piscivorous walleye and yellow perch in Saginaw Bay, indicating that trout‐perch are a weak conduit of energy transfer to higher trophic levels.